Biodiversity and resilience interventions: Analysis of interviews with farmers in Germany - Kuncz, Adina; Lambarraa-Lehnhardt, Fatima; Zander, Peter; Zhang, Wei (International Food Policy Research Institute, 2022)
This note summarizes the results of interviews with 18 farmers in Germany to identify the motivations and challenges that impact farmers’ adoption of practices that improve biodiversity. All interviews were conducted either by phone or on Zoom. Respondents were identified through contacts provided by Bayer AG, the Leibniz Centre for Agricultural Landscape Research (ZALF) networks, local farmers as-sociations, an online list of apprenticing farms, and the farmer network of the team leader based at ZALF, and thus were not representative. The interviews were part of the Enhancing Biodiversity and Resilience in Crop Production project, which was commissioned by Bayer and implemented in collabo-ration with ETH Zurich and IFPRI. The project analyzed information that can contribute to guidance on using agricultural practices to improve biodiversity and resilience of farming systems. It focused on in-tensive maize, wheat, and soy production systems in France, Germany, Brazil, and the United States.